Small Organic Farm Renewable Energy Demonstration Project Based on Incremental Capital Investment and Community Participation - Anna E. Demeo; Michael L. Peterson (Journal of Agriculture, Food Systems, and Community Development, 2016)
Rising fuel prices, energy security, and climate-change awareness are all incentives for farmers to implement efficiency measures and renewable energy systems, such that all or part of a farm's energy needs are produced locally. This practice, known as clean energy farming, complements principles of sustainable agriculture such as promoting environmental stewardship, reducing dependence on nonrenewable resources, increasing economic viability, and strengthening farm families and society as a whole. Farmers who entertain moving toward a more sustainable energy portfolio are often unsure where to begin and how to approach such an endeavor. This uncertainty, combined with the perceived enormity of the task, create an insurmountable roadblock for many. Overcoming these barriers and engaging in small-scale renewable energy projects can benefit the farmer and the larger community. Exposure to such projects is an invaluable means of fostering support for renewable energy as it helps the public better appreciate the human ecological connection between daily energy consumption, the source of that energy, and the overall effect on the environment.